2018
DOI: 10.1093/jn/nxy071
|View full text |Cite
|
Sign up to set email alerts
|

Higher Longitudinal Milk Intakes Are Associated with Increased Height in a Birth Cohort Followed for 17 Years

Abstract: IFS participants' height increased by 0.39 cm for each additional 8 ounces (236 mL) of milk consumed throughout childhood and adolescence. The clinical implications of the mild linear growth faltering observed in healthy youth are unknown. This trial was registered at www.clinicaltrials.gov as 199112665.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 26 publications
0
23
0
1
Order By: Relevance
“…For example, a systematic review from Hornell et al [ 46 ] concluded that there was only limited suggestive evidence that the intake of animal protein, especially from dairy, has a stronger association with growth than vegetable protein. Further, a recently published longitudinal study by Marshall et al [ 39 ] reported that milk intake adjusted for mean adequacy ratio, energy intake, and baseline socioeconomic status was associated with height throughout childhood and teenage years. However, a common factor shared by these reports is that they include data from a much broader age range than is addressed in our review and this may have had an impact on outcomes.…”
Section: Dairy Intake and Linear Growth In Preschool Childrenmentioning
confidence: 99%
“…For example, a systematic review from Hornell et al [ 46 ] concluded that there was only limited suggestive evidence that the intake of animal protein, especially from dairy, has a stronger association with growth than vegetable protein. Further, a recently published longitudinal study by Marshall et al [ 39 ] reported that milk intake adjusted for mean adequacy ratio, energy intake, and baseline socioeconomic status was associated with height throughout childhood and teenage years. However, a common factor shared by these reports is that they include data from a much broader age range than is addressed in our review and this may have had an impact on outcomes.…”
Section: Dairy Intake and Linear Growth In Preschool Childrenmentioning
confidence: 99%
“…One group (42) evidenced this effect specifically in the subset of children who started with a lower height-for-age z score at the beginning of the intervention, which could support this hypothesis, although this may not have been adequately explored in the articles cited. Nevertheless, 1 cohort study by Marshall et al (31), not included in the review, also suggested a relation between milk consumption and height increase, although in this case the children who participated belonged to families of medium socioeconomic status, with low risks of malnutrition. However, this relation was nonlinear; therefore, the mechanism that could explain the beneficial effect could not be attributed exclusively to this dietary measure but may link to a more favorable environment involving other unevaluated factors.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding sex, the present review found that studies on girls obtained less significant results for height than did those on both boys and girls, but studies using both sexes showed no differences between the sexes. Some cohort studies that included both boys and girls found statistically significant differences in height relative to dairy intake but also found no differences between subgroups by sex (31,55). However, a study on height in adult males from 48 European countries found that the ratio of high-quality protein intake, especially from dairy products, to low-quality proteins from wheat was the most important factor in the secular improvement of height (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data used in the current descriptive model analyses were collected as part of the Iowa Fluoride Study (IFS), a longitudinal birth cohort study that investigated fluoride intakes, dietary intakes, and oral health. [21][22][23][24][25] This manuscript was prepared in accordance with STROBE guidelines. IFS questionnaires queried family demographics at birth (1992)(1993)(1994)(1995) and in 2007 and participant beverage intakes, fluoride intakes, and oral hygiene behaviors at 3-to 6-month intervals following birth.…”
Section: Data Collectionmentioning
confidence: 99%